[PP.17.08] INTER-ARM BLOOD PRESSURE DIFFERENCE AND RISKS OF COGNITIVE DECLINE. A 9-YEAR PROSPECTIVE COHORT STUDY OF OLDER ADULTS. (September 2016) - THOMAS, D.; Clark, C.; Llewellyn, D.; Ferrucci, L.; Campbell, J.
Abstract : Objective: In the UK 7% of those aged over 65 have dementia. Current interventions to treat dementia are of limited efficacy therefore prevention and pre-symptomatic detection are important. Systolic inter-arm differences (IAD) in blood pressure (BP) >/=10 mmHg are associated with increased cardiovascular mortality. Both Alzheimer's disease and vascular dementia include vascular disease in their aetiology. We hypothesised that IAD may also be prospectively associated with increased risks of cognitive decline. Design and method: InCHIANTI is a prospective study of ageing in older Italian adults. Participants undergo a detailed medical history and examination at recruitment and at 3 yearly follow up intervals. Assessments include sequential bilateral BP readings and cognitive assessments including Mini Mental State Examinations (MMSE). Those exhibiting a decline in MMSE >/=5 points over follow up were considered to exhibit substantial cognitive decline. We used univariable cross-sectional and regression analyses to explore associations between IAD, mortality, cognitive decline, and rate of change in MMSE over time. Significant univariable associations, and known cardiovascular or dementia epidemiological risk factors, were combined in a multivariable model. Results: There were 1, 142 participants without dementia at baseline. On univariable analysis risks of substantial cognitive decline were non-significantly higher with an IAD >/=10 mmHg at each of the follow-up assessments (RR 1.6 (95% CI 1.0 to 2.5) at 3 years, 1.2 (0.8 to 1.9) at 6 years and 1.3 (0.9 to 1.8) at 9 years). Mean rate of decline in MMSE scores was higher at 0.5 points per year with an IAD >/=10 mmHg compared to 0.3 per year for IAD <10 mmHg (p = 0.02). On multivariable modelling no significant associations of cognitive decline with IAD were observed. Conclusions: To our knowledge this is the first report examining the association of IAD with cognitive decline. Our findings suggest a potential association of IAD with higher rates of cognitive decline. IAD in this study was measured by a sequential method, which we have found to underestimate survival associations compared to simultaneous measurement techniques. Therefore further studies using robust methods of measurement are indicated to clarify whether detection of an IAD can predict future substantial cognitive decline.